A global system for monitoring radiative transfer and directional temperatures over heterogeneous surfaces - Shouyi Zhong; Zunjian Bian; Roujean Jean-Louis; Qiang Liu; Juan Cheng; Yongming Du; Hua Li; Jianguang Wen; Qing Xiao (Remote Sensing of Environment, 2026)

Multifunctional Fe-biochar for simultaneously enhancing methanogenesis and mitigating membrane fouling in anaerobic membrane bioreactor treating brewery wastewater - Xue Li; Zi Song; Yanning Wang; Qing Du; Qian Wang; Zhiwen Wang; Guojin Li; Wenshan Guo; Huu Hao Ngo; Xinbo Zhang (Bioresource Technology, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Antibiotic-induced photosynthetic dysfunction in wheat: Coupled inhibition of light reactions and carbon assimilation revealed by multi-omics - Jin Wu; Wen Ye; Jiayin Zhou; Yaxin Zhu; Qing Wei; Zhiheng Li; Lidan Wu; Huijun Liu; Shaoting Du (Environmental Pollution, 2026)

Prokaryotic Argonautes as programmable tools for foodborne biological hazards detection: mechanisms, applications, and prospects - Jing-bo Jiao; Cheng-long Zhao; Jiang-li Cao; Tong Lin; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Critical Reviews in Food Science and Nutrition, 2026)

Divergent efficacy of attapulgite versus straw biochar for heavy metal passivation during sewage sludge vermicomposting - Zhong Chuang; Li Nan; Tian Geilin; Wang Jitao; Meng Hongying; Du Qing; Meng Fansheng; Qiu Chunsheng; Wang Shaopo; Bi Yanmeng (Journal of Environmental Chemical Engineering, 2026)

Natural deep eutectic solvent-extracted propolis bioactives and ZIF-L integrated PVA films for active packaging and oyster preservation - Tian Du; Qing-Ping Zheng; Ye-Ting Wang; Meng Li; Yan-Zhen Zheng (Food Research International, 2026)

Dual role of cold plasma in suppressing the growth, remodeling cellular ultrastructure and stimulating metabolic response of Kazachstania exigua from transcriptomic insight - Binyao Wang; Qing Du; Liangpeng Yuan; Longhua Pan; Yi Tang; Menglu Yang; Wenjian Wang; Dengshui Peng; Huajia Li; Shan Zeng; Lihong Ge; Jianping Yang; et al. (Food Research International, 2026)

Earthquake-induced displacement model for earth slopes incorporating soil softening effect based on material point method - Yu-Han Zhao; Qiang Wu; Zhi-Yong Fu; Dian-Qing Li; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2026)

Preservation methods affect community recovery in soil nematode metabarcoding - Fan Guo; Kemei Li; Hongrui Du; Olivera Topalović; Hongmei Li; Xue Qing (Rhizosphere, 2026)

2-Undecanone controls pepper anthracnose by simultaneous activation of host resistance and direct antifungal action - Yixin Wang; Shijun Wang; Xin Yan; Xiangsheng Li; Chunyuan Cheng; Sansheng Geng; Bin Chen; Heshan Du; Qing Wang; Xiaofen Zhang (Food Microbiology, 2026)

Mechanism of hydrophobic modification-induced reduction in matric suction on the inhibition of crack development in expansive soil under wet-dry cycles: Insights from molecular dynamics simulation - Xiang Gao; Huie Chen; Mai Sawada; Hua Du; Jinfeng Li; Qing Wang; Jinzhong Zhu; Qi Ding (Engineering Geology, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Utilizing steel slag carbonation to mitigate soil dispersibility: Dual benefits of carbon sequestration and soil stabilization from industrial solid waste - Huie Chen; Yonggui Luo; Hua Du; Qing Wang; Qingbo Yu; Jishuai Zhu; Sitan Li (Chemical Engineering Journal, 2026)

Description of Sulfitobacter gelatinilyticus sp. nov. and Sulfitobacter weihaiensis sp. nov., isolated from marine sediment - Jing Zhang; Zou-Yu Jin; Hai-Qing Zhang; Zi-Hao Wan; Yuan-Xi Xiao; Hui-Xing Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2026)

Mechanochemistry-driven acid-free strategy for synergistic recycling of mixed spent lithium-ion batteries - Kaiyuan Fang; Jialin Qing; Jiawei Du; Guopeng Yang; Guiqing Zhang; Wenjuan Guan; Mingyu Wang; Shengxi Wu; Xinsheng Wu; Qinggang Li (Waste Management, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Corrigendum to “Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines”, J. Hazard. Mater. (2026) 142537 - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Gravity-assisted dual-mode biosensor based on CbAgo-driven gel-sol transition of DNA hydrogels for Salmonella detection - Jing-bo Jiao; Cheng-long Zhao; Bei-bei Tian; Jiang-li Cao; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Chemical Engineering Journal, 2026)

Seismic displacement and failure characteristics of rock slopes considering dynamic degradation of rock structural planes under pulse-like ground motions - Shuang Xiong; Dian-Qing Li; Zhiyong Fu; Wenqi Du (Bulletin of Engineering Geology and the Environment, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Integrating digital PCR and metagenomics to quantify potential soilborne bacterial pathogens in urban ecosystem - Tong Li; Kai Feng; Shang Wang; Xiongfeng Du; Jingjing Li; Songsong Gu; Bo Zhao; Xingsheng Yang; Xi Peng; Qing He; Yingcheng Wang; Danrui Wang; et al. (Journal of Hazardous Materials, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Pesticide beta-cypermethrin impairs endometrial decidualization and embryo implantation by suppressing autophagy through oxidative stress - Li-Qing Wang; Huang-Nian You; Qiong-Jun Xu; Wen-Jie Yu; Xiao-Mei Wu; Xiao-Qing Pang; Xiao-Xi Chen; Wen-Bin Du; Qian-Feng Qiao; Jing-Ai Li; Yu-Meng Zhou; Yong-Jiang Zhou (Chemico-Biological Interactions, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Targeted lithium extraction from spent LiNixCoyMnzO2 cathode material by CO2 hydrothermal method - Kaiyuan Fang; Wenjuan Guan; Jiawei Du; Huan Li; Jialin Qing; Guiqing Zhang; Guan Peng; Mingyu Wang; Shengxi Wu; Xinsheng Wu; Qinggang Li (Journal of Environmental Chemical Engineering, 2026)

Genomic functional annotation of ATP-binding cassette (ABC) transporter genes with emphasis on the formation of wax layer in Phenacoccus solenopsis - Qian-Kun Du; Xin-Hua Ding; Wen-Chao Guo; Guo-Qing Li (Journal of Asia-Pacific Entomology, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Shear flow alleviates spaceflight-induced hepatic lipid dysregulation via suppression of SREBP mechanotransduction - Ning Li; Xiaoyu Zhang; Huan Luo; Jin Zhou; Yu Du; Ziliang Zhang; Dongyuan Lü; Yan Zhang; Shouqin Lü; Qing Luo; Guanbin Song; Shujin Sun; et al. (Science Bulletin, 2026)

Structural safety and energy performance of floating offshore photovoltaic systems with stochastic anchor position deviations - Tao Jin; De-Qing Zhang; Jun-Feng Du; Yu Li; Hua-Jun Li (Ocean Engineering, 2026)

The fate and risk of chromium in lignin-rich Cr-Fe coprecipitates: How formation pathways dictate dissolution and reoxidation stability - Xue Du; Jiaxin Li; Qing Yang (Journal of Hazardous Materials, 2026)

Ecological network construction and resilience optimization of coastal zones in megacity clusters: A case study of the Guangdong–Hong Kong–Macao Greater Bay Area - Yilin Huang; Hui Li; Yun He; Qing Xu; Lixia Liao; Han Sheng; Jiaheng Du (Ecological Engineering, 2026)

Characterization of dynamic behavior of clay-gravel mixtures under high cyclic strains in undrained triaxial conditions - Qiming Chen; Shun Wang; Dian-Qing Li; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2026)

Micropillar-patterned electrodes to enhance mass transfer in low Pt-loaded fuel cells - Yuan Wang; Linhao Fan; Yongkang Luan; Qing Du; Yalin Zhang; Xing Li; Meng Ni; Fang Liu; Zhongjun Hou; Kui Jiao (Science Bulletin, 2026)

Dynamic analysis of the flexible conveying pipe in a new seabed levelling system - Jun-Feng Du; Cheng-Xin Li; De-Qing Zhang; Jin-Long Duan; Xian-Dao Feng (Ocean Engineering, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenols from Macadamia integrifolia green peel: COSMO-RS screening, process optimization, and its application in chitosan/polyvinyl alcohol films - Ming Zhang; Yang Yang; Jian Qiao; Ya Li; Ran Kong; Jianfei Kuang; Lingdong Li; Changbin Wei; Xu Deng; Li-qing Du; Xixiang Shuai (Food Chemistry, 2026)

Bioactive biphasic textile scaffold for spatiotemporal regulation of inflammation and osteogenesis in enthesis healing during anterior cruciate ligament reconstruction - Meilin Song; Yanran Du; Haohan Li; Jiankun Feng; Xianchao Li; Yakun Huang; Yu-Qing Zhao; Chengbo Li; Huanhuan Yan; Dongsheng Li; Xiumei Mo; Guige Hou; et al. (Chemical Engineering Journal, 2026)

Few-Shot intelligent identification of rock thin sections based on SAM - Yuan Zhou; Qing Li; Zhuofeng Zhang; Zhengyu Wei; Qiang Du; Xinlong Li (Earth Science Informatics, 2026)

Metagenomics reveals potential antimicrobial peptides in Chinese baijiu fermentation - Rubing Du; Xue Li; Yan Xu; Kexin Jing; Ling Ao; Bo Deng; Qing Xu; Ping Song; Jing Yu (Food Microbiology, 2026)

Strain localization in rock: From multi-scale measurement to AI-driven prediction - Shijiao Yang; Qing Du; Jianchang Yan; Wenhua Liu; Jiancheng Huang; Danli Li (Engineering Geology, 2026)

Deformation Behavior and Shakedown Response of Subgrade Soils Under Cyclic Loading - Hailan Zhang; Yefeng Du; Yong Huang; Xiaoning Zhang; Ren Zou; Qing Jin; Linjie Zhang; Xiangyang Li (Geotechnical and Geological Engineering, 2026)

Spent LiFePO4 batteries valorization: integrated process for battery-grade FePO4 production - Jiawei Du; Jialin Qing; Guiqing Zhang; Zuoying Cao; Qinggang Li; Mingyu Wang; Wenjuan Guan; Shengxi Wu; Xinsheng Wu (Waste Management, 2026)

Dispersivity-induced crack patterns in soils subjected to combined wet-dry and freeze-thaw cycles: Insights from monitoring, testing, and CT scanning - Hua Du; Huie Chen; Jinfeng Li; Qing Wang; Fansheng Kong; Boxin Wang; Wenhua Wang (Soil and Tillage Research, 2026)

The recycling of spent lithium iron phosphate batteries: A review on current progresses and technologies from an industrial utilization perspective - Jiawei Du; Guiqing Zhang; Jialin Qing; Kaiyuan Fang; Zuoying Cao; Qinggang Li; Mingyu Wang; Wenjuan Guan; Xinsheng Wu; Shengxi Wu (Journal of Cleaner Production, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Antibacterial properties and mechanisms of anti-lipopolysaccharide factor 1 from Procambarus clarkii - Qing Yang; Zhengyan Du; Lin Yang; Yujing Jia; Xinru Wang; Hao Li; Libo Hou; Lei Zhu; Xianghui Kong (Fish & Shellfish Immunology, 2026)

The role and therapeutic potential of purinergic signaling pathway in metabolic syndrome-related atherosclerosis - Xiang Li; Chengxin Gong; Chengxiao Fu; Qing Xia; Yue Zhang; Yue Du; Yuting Sun; Hong Xu (Purinergic Signalling, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Molecular mechanisms of cold stress-induced energy stress, cholesterol metabolic disorders, and apoptosis in Pangasianodon hypophthalmus - Dongjie Wang; Min Li; Min Liao; Yao Tian; Qing Wu; Shaolin Xie; Wei Luo; Jixing Zou; Jun Shi; Zongjun Du (Aquaculture, 2026)

Electrospun nanofiber electrodes for low platinum-loaded fuel cells - Linhao Fan; Yongkang Luan; Lei Xing; Qing Du; Jin Xuan; Yuan Wang; Fan Zhang; Xing Li; Shuheng Yuan; Chasen Tongsh; Siyuan Wu; Kui Jiao (Science Bulletin, 2026)

Advances in direct seawater electrolysis for green hydrogen production: emerging technologies and future perspectives - Ruihao Lu; Bowen Wang; Lincai Li; Zhiming Bao; Bin Li; Qing Du; Kui Jiao (Science Bulletin, 2026)

Characterisation of microbial succession and exploration of the stability maintenance strategy of phage community on microbes in radish paocai - Menglu Yang; Yuli Huang; Jiaqi Liu; Guangqiang Wang; Yuan Mei; Lihong Ge; Qing Du; Huajia Li; Nan Zhao (International Journal of Food Microbiology, 2026)

Nitric oxide mitigates selenium phytotoxicity in barley: Inhibiting selenium absorption, altering selenium distribution, and strengthening the antioxidant system - Chao Cheng; Yunxin Yi; Qing Li; Huirong Yang; Teodora Emilia Coldea; Haifeng Zhao; Gijs Du Laing (Plant Science, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Synergistic enhancement of tetracycline photodegradation in 5 % Ce-doped Bi₂O₃–Co₃O₄/C: Oxygen vacancy-mediated band engineering and singlet oxygen pathway optimization - Xiaoqing Wang; Weiyi Li; Junhao Zhang; Jiangman Zheng; Tuo Li; Cong Du; Xuan Luo; Zhitao Ai; Chennan He; Shanjun Mao; Rongbo Zheng; Qing Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Analysis of the time-varying reliability of earth dam slopes considering multiparameter spatial variability - Zhi-Ping Deng; Yi Zou; Wenqi Du; Dian-Qing Li; Mao-Xin Wang; Shui-Hua Jiang (Computers and Geotechnics, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Transcriptome and physiological analysis revealed core genes that promote glutathione metabolism in blue honeysuckle in response to freezing stress - Yuxin Fan; Dandan Zang; Tianyi Wang; Zhihua Song; Na Li; Hongyan Cao; Tingting Du; Meng Qi; Yujie Fu; Qing Yang; Biying Dong; Dong Meng (Tree Genetics & Genomes, 2025)

Sedimentary model evolution and palaeoenvironmental significance of the Upper Ediacaran microbial dolomites - Yuan Zhou; Xuelian You; Qing Li; Zhuofeng Zhang; Qiang Du; Zhengyu Wei; Xinlong Li; Hui Zhou (Precambrian Research, 2025)

EPA-enriched phospholipids and DHA-enriched phospholipids prevent dexamethasone-induced skeletal muscle atrophy via regulating protein turnover and mitochondrial quality - Ying-Chao Li; Shi-Xiang Wu; Qing-Yan Zou; Yan Zheng; Zi-Jian Wu; Xin-Yue Zhao; Xiang Gao; Yu-Hong Yang; Lei Du (Food Research International, 2025)

Facilitating carrier kinetics in dual S-Scheme heterojunctions through interface regulating strategy for H2O2 generation and nizatidine degradation - Sheng Liu; Yanjun Zhang; Jun Du; Yuan Xue; Cheng Huang; Zushun Xu; Peng Wang; Zhengrong Wei; Zhanhui Yuan; Guangfu Liao; Qing Li (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

A line-spread kernel function for angular anisotropy in row-dominated heterogeneous scenarios - Yifan Lu; Zunjian Bian; Chandrika Pinnepalli; Jean-Louis Roujean; Mark Irvine; Xinguang Sang; Xiaobo Luo; Hua Li; Yongming Du; Biao Cao; Qing Xiao (Remote Sensing of Environment, 2025)

Physics-guided multimodal deep learning reveals determinants of rock brittleness across scales - Qing Du; Xiaoju Kuang; Jiancheng Huang; Jincheng Liang; Danli Li; Shijiao Yang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Metal-organic framework ZIF-67 derived Co@CN catalysts for the promising generation of hydrogen from ammonia decomposition - Tianxiang Li; Xiaofeng Gu; Qing Wang; Kailong Zhang; Wanze Li; Hong Du; Hewen Liu; Emin Aili; Yufang Ye; Xiao Chen (Fuel, 2025)

Canopy and understory nitrogen addition differentially regulate fine root decomposition in a temperate forest - Xiaowei Li; Chenlu Zhang; Beibei Zhang; Li Jiang; Chenhui Sun; Yulong Bai; Yifei Shi; Wei Zhang; Qing Ye; Junhua Yan; Juemin Fu; Wenzhi Du; et al. (Forest Ecology and Management, 2025)

Fabrication of Au@PAM microspheres by coaxial electrospray for radiofrequency ablation and transcatheter artery embolization in hepatocellular carcinoma - Jiaojiao Li; Lei Chen; Boliang Zhou; Xin Yang; Xingyu Chen; Zhiwei Lu; Jiangling Wan; Qing Du; Chuansheng Zheng; Yanbing Zhao; Xiangliang Yang (Chemical Engineering Journal, 2025)

Collaborative passivation of defects and enhancing crystallization enabled by an additive with multiple active sites for inverted perovskite solar cells - Qing Du; Shangwei Feng; Yue Liang; Bufan Yu; Jiacheng Liu; Yihang Li; Wei Hong; Lei Wang; Guichuan Xing; Jiangshan Chen; Dongge Ma (Chemical Engineering Journal, 2025)

Single cell protein production of co-culture Kodamaea ohmeri and Lactococcus lactis in corn straw hydrolysate - Yong-Qiang Yang; Xu Li; Zhen-Zhi Wang; Xiao-Yan Huang; Du-Wen Zeng; Xin-Qing Zhao; Zhi-Qiang Liu; Feng-Li Zhang (Bioresource Technology, 2025)

Dual-signal enhanced lateral flow immunoassay with nanobody-functionalized magnetofluorescent nanoprobes for multiplexed detection of foodborne pathogens - Wenjin Hu; Shengyang Wang; Qing Du; Shixiang Yang; Xiaxia Wei; Xi Li; Huai Lin (Analytica Chimica Acta, 2025)

Effects of AMPEP (Ascophyllum marine plant extract powder) and SJEP (enzymatic extracts of Saccharina japonica) on growth and resistance of red macroalga Pyropia yezoensis - Guo-Ying Du; Li-Hong Ma; Yu-Qing Wang; Xin-Yu Zhang; Yan-Jun Gong; Dong-Mei Wang (Algae, 2025)
Seaweed extracts are widely used as biostimulants in terrestrial crops but remain underexplored for economic macroalgae. This study investigated the effects of Ascophyllum marine plant extract powder (AMPEP) and Saccharina japonica extract powder (SJEP) on the growth and stress resistance of Pyropia yezoensis, a commercially significant red macroalga along the Northeast Asia coast. Through gradient analysis, optimal concentrations were determined to be 0.05 g L−1 for SJEP and 0.1 g L−1 for AMPEP, based on their effects on daily growth rate (DGR) and photosynthetic performance. Both extracts significantly improved resistance to red rot disease, reducing lesion area while increasing DGR, photosynthetic efficiency, and pigment content compared to the control. Additionally, SJEP and AMPEP elevated superoxide dismutase (SOD) activity and suppressed malondialdehyde (MDA) accumulation. Under cold stress, the extracts mitigated declines in DGR, photosynthetic parameters, pigment levels, and SOD activity, while restraining MDA elevation. Notably, the expression of cold-responsive genes (PyABCC1 and PyABCI1) peaked in SJEP treatment and remained elevated in AMPEP treatment, surpassing the control by several-fold. Overall, SJEP outperformed AMPEP, likely due to its higher polysaccharide and polyphenols. These results support brown algal extracts—particularly enzymatic extracts—as practical biostimulants to enhance growth, disease resistance, and cold tolerance in P. yezoensis cultivation.

Anti-disintegration property of red soil treated with building gypsum powder - Yinlei Sun; Zhen Li; Xuan-Chen Lin; Qing-Ru Du; Xi Zou; Xianwei Zhang (Applied Clay Science, 2025)

Improved satellite-scale land surface temperature components retrieval with hotspot effect correction and temperature difference constraints - Yifan Lu; Zunjian Bian; Jean-Louis Roujean; Hua Li; Frank M. Göttsche; Yajun Huang; Tengyuan Fan; Biao Cao; Yongming Du; Qing Xiao (Remote Sensing of Environment, 2025)

Energy consumption and quality improvement of frozen pork using NaCl refrigerant with three amino acids in contact immersion freezing - Yu Zhou; Qiong Pan; Wen Li; Lifang Zou; Qing-fei Du; Wu Wang; Cong-gui Chen (Meat Science, 2025)

Investigating the Potential Therapeutic Targeting of the JAK-STAT Pathway in Cerebrovascular Diseases: Opportunities and Challenges - Jia-Wei Wu; Bing-Xin Wang; Li-Ping Shen; Yong-Lin Chen; Zhi-Yong Du; Shi-Qing Du; Xiao-Jie Lu; Xu-Dong Zhao (Molecular Neurobiology, 2025)

Metabolomic analysis of blood spots in a Chinese cohort with autism spectrum disorders: a pilot study - Hui Wang; Li Ding; Zheng-huan Mao; Yu Du; Qing-mei Han; Jia-yu Xu; Fei-fei Peng; Hai-feng Li; Chao-chun Zou (Metabolic Brain Disease, 2025)

Potential viral influence on sulfur metabolism in acid sulfate soils - Li Bi; Shuai Du; Rob Fitzpatrick; Qing-Lin Chen; Thi Bao-Anh Nguyen; Zi-Yang He; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

Elevated globally rock weathering carbon sinks driven by reduced snow cover - Lian Xiong; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Yue Li; Luhua Wu; Junhan Li; Chen Ran; Sirui Zhang; Jingjing Liao; Xiaodong Yuan; Chaochao Du; et al. (Science Bulletin, 2025)

Isolation and characterization of a novel Paenibacillus species from high-salt environment with broad-spectrum antimicrobial activity against food spoilage microorganisms - Fei Han; Danni Tong; Zixuan Guo; Zhen Li; Zhidong Zhang; Rubing Du; Qing Xu (Food Bioscience, 2025)

Probabilistic inversion of shear wave velocity profile based on the dispersion curve from multichannel analysis of surface waves and inequality constraints on layer thicknesses - Xuan-Hao Wang; Zi-Jun Cao; Tengfei Wu; Wenqi Du; Dian-Qing Li (Engineering Geology, 2025)

Origin of the light-promoted synergy among active surface/interface oxygen, water adsorption sites and basic sites on NiCo/Al3+ doped MgO for efficient photothermocatalytic cellulose steam reforming - Qing Du; Mengqi Zhong; Yuanzhi Li; Jichun Wu; Cong Ji (Chemical Engineering Journal, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Enhancing sensory acceptance of roasted flaxseeds: The role of degumming and roasting conditions - Jun-le Li; Yang-qing Xiao; Yue Du; Jia-hui Yu; Martin J.T. Reaney; Yong Wang; Zi-zhe Cai (Food Chemistry, 2025)

Rural depopulation has reshaped the plant diversity distribution pattern in China - Qing Luo; Cuiwei Zhao; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; Yingying Xue; Mingkang Long; et al. (Resources, Conservation and Recycling, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

Response of carbonate rock weathering carbon sink to seismic peak ground acceleration in China - Minghui Li; Qiu Tan; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; Yingying Xue; Mingkang Long; et al. (Global and Planetary Change, 2025)

The Effect of Urbanization and Farmland to Forests Program on Surface Runoff - Jing Zhang; Zi-Jing Chen; Yong Ma; Qing Xie; Wen-jie Li; Hong-bo Du (Water Resources Management, 2025)

Global impacts of land use on terrestrial carbon emissions since 1850 - Xiaodong Yuan; Xiaoyong Bai; Zhongfa Zhou; Guangjie Luo; Junhan Li; Chen Ran; Siri Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Lei Dai; Zilin Li; et al. (Science of The Total Environment, 2025)

Investigation into the mechanical properties and microscopic mechanisms of dispersive saline soil improved by environmentally friendly biopolymers - Xin Xu; Jinlong Li; Qing Wang; Hongnan Chu; Haomin Lei; Xinhai Wang; Lingjia Meng; Zhao Ruan; Hua Du (Journal of Environmental Chemical Engineering, 2025)

Deep removal of minor silicon in the crude nickel sulfate solution by solvent extraction of Si-Mo heteropoly acid - Xi Zhong; Jiawei Du; Jialin Qing; Xinsheng Wu; Qingang Li; Mingyu Wang; Wenjuan Guan; Shengxi Wu; Guiqing Zhang (Journal of Environmental Chemical Engineering, 2025)

Impact and mechanism of polyethylene terephthalate microplastics with different particle sizes on sludge anaerobic digestion - Qing Yang; Jiaxin Li; Linlin Ma; Xue Du (Environmental Pollution, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Driving force shapes the biocake characteristics in membrane-based bioreactors - Jing-Xiao Zhang; Yu-Sheng Li; Wen-Jie Du; Tian Tian; Liang Xuan; Han-Qing Yu (Water Research, 2025)

Development and verification of subgrade service performance test system considering the principal stress rotation - Zhenhao Bao; Xinzhuang Cui; Yefeng Du; Qing Jin; Jianwen Hao; Tiancai Cao; Xiangyang Li; Xiaoning Zhang (Transportation Geotechnics, 2025)

Kinetic analysis on the hydrogen cyanide formation in the premixed methane/ammonia flame - Du Wang; Zhen-Yu Tian; Qing-Li Li; Jiu-Jie Kuang; Xu-Peng Yu (Fuel, 2025)

Modulation of phase separation and molecular stacking in ternary organic solar cells by introducing a guest polymer with excellent miscibility with host polymer - Xiaoru Xu; Zongtao Wang; Chao Li; Mengzhen Du; Qing Guo; Erjun Zhou (Chemical Engineering Journal, 2025)

Intelligent electric energy driven ultrathin Graphene-Based Janus Films: Pioneering design for dynamic Electrochromism and superior microwave absorption - Tian Li; Jiatong Li; Zhengkang Xu; Jinzhe Li; Tinghao Liao; Jiani Du; Shanshan Wang; Qing Qi; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2025)

Bismuth-based porphyrin metal organic framework specific nano-inducer for tumor photoimmunotherapy - Jiacheng Lu; Qian Wang; Ju Du; Sijia Wu; Qing Miao; Yuhao Li; Yuqing Miao; Jingxiang Wu (Chemical Engineering Journal, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

Knockdown of DJ-1 Exacerbates Neuron Apoptosis Induced by TgCtwh3 through the NF-κB Pathway - Di Yang; Minmin Wu; Nian Zou; Yiru Tang; Qing Tao; Lei Liu; Mengmeng Jin; Li Yu; Jian Du; Qingli Luo; Jilong Shen; Deyong Chu; et al. (Molecular Neurobiology, 2025)
Mutations or loss of function of DJ-1 and Toxoplasma gondii ( T. gondii ) infection has been linked to neurodegenerative diseases, which are often caused by oxidative stress. However, the relationship between DJ-1 and T. gondii infection is not yet fully understood. Therefore, this study aimed to investigate the expression of DJ-1 in the hippocampus tissue of mice or in HT22 infected with T. gondii Chinese 1 genotype Wh3 strain (TgCtwh3) and the effect of DJ-1 knockdown on neuronal apoptosis induced by TgCtwh3 tachyzoite, as well as the underlying mechanism at the cellular and molecular level. Firstly, we detected DJ-1 protein expression and cell apoptosis in the hippocampal tissue of mice infected by TgCtwh3. Then, we examined DJ-1 expression and apoptosis in HT22 challenged with TgCtwh3. Finally, we evaluated the apoptosis in HT22 with DJ-1 knockdown which was infected with TgCtwh3 and assayed the expression of NF-κBp65 and p -NF-κBp65. Our results showed that DJ-1 expression was reduced and neurons underwent apoptosis in the hippocampus of mice infected with TgCtwh3 tachyzoites. Additionally, the knockdown of DJ-1 followed by infection with TgCtwh3 tachyzoites led to increased apoptosis in HT22 cells through the NF-κB signaling pathway. Therefore, this study suggests that DJ-1 is an important target for preventing apoptosis caused by T. gondii TgCtwh3.

An in-situ biochar-enhanced anaerobic membrane bioreactor for swine wastewater treatment under various organic loading rates - Nianwen Chen; Xinbo Zhang; Qing Du; Huizhong Wang; Zhiwen Wang; Junzhi Ren; Hongxia Li; Wenshan Guo; Huu Hao Ngo (Journal of Environmental Sciences, 2024)

The restoration of karst rocky desertification has enhanced the carbon sequestration capacity of the ecosystem in southern China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Jinfeng Wang; Luhua Wu; Chaojun Li; Junhan Li; Yuanhuan Xie; Chen Ran; et al. (Global and Planetary Change, 2024)

Valorizing Arthrospira cell residues into polysaccharides: Characterization and application in yogurt - Genyuan Li; Qing Guo; Qian Chen; Kefan Ouyang; Hexiang Xie; Hua Xiong; Yulan Du; Qiang Zhao (Food Chemistry, 2024)

A novel in-silico strategy for the combined inhibition of intestinal bacterial resistance and the transfer of resistant genes using new fluoroquinolones, antibiotic adjuvants, and phytochemicals - Qikun Pu; Zhonghe Wang; Tong Li; Qing Li; Meijin Du; Wenwen Wang; Yu Li (Food Bioscience, 2024)

Seismic performance assessment of high arch dams considering the pulse-like and directionality effects of near-fault ground motions - Gang Wang; Shao-Dong Yan; Dian-Qing Li; Wenqi Du (Engineering Structures, 2024)

Polyoxometalate oxate solution: An electrolyte additive to sustainably improve the anodes electrode of aqueous Zn ion batteries - Li-li Du; Zhuo Li; Wei-jia Song; Qing-peng Bao; Peng-fei Wang; Zhe Gong; Yu-hang Zhang; Yu-han Wu; Fa-nian Shi; Ming-dong Zhou; Kai Zhu (Chemical Engineering Journal, 2024)

Simplicispira sedimenti sp. nov., isolated from a sediment of drainage ditch in winery - Xing Chen; Yuan-Dong Li; Xiu-Ming Liu; Li Gao; Xing-Kui Zhou; Li-Min Dong; Gang Du; Neeli Habib; Wen-Jun Li; Yan-Qing Duan (Antonie van Leeuwenhoek, 2024)

Influence of surface water and groundwater gradient on spatial distribution of typical vegetation in the hinterland of Taklamakan desert - Lei Peng; Yan-Bo Wan; Hao Li; Men-Di Du; Qing-Dong Shi (Science of The Total Environment, 2024)

An integrated method for angular and temporal reconstruction of land surface temperatures - Zunjian Bian; Shouyi Zhong; J.-L. Roujean; Xiangyang Liu; Sibo Duan; Hua Li; Biao Cao; Ruibo Li; Yongming Du; Qing Xiao; Qinhuo Liu (Remote Sensing of Environment, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Unexpected response of terrestrial carbon sink to rural depopulation in China - Qing Luo; Xiaoyong Bai; Cuiwei Zhao; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; Yingying Xue; et al. (Science of The Total Environment, 2024)

Contribution to energy conservation and quality improvement of frozen pork via contact/contactless immersion freezing in NaCl solution - Yu Zhou; Xia Yu; Ran Xiao; Li-fang Zou; Qing-fei Du; Fei Ma; Cong-gui Chen (Meat Science, 2024)

Complete recovery of rare earths from waste LYSO crystals by thermal shock treatment and reinforcement decomposition - Xi Zhong; Jialin Qing; Sidan Deng; Jiawei Du; Li Zeng; Qinggang Li; Guiqing Zhang; Shengxi Wu (Journal of Environmental Chemical Engineering, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

CAFs-derived Exosomal miR-889-3p Might Repress M1 Macrophage Polarization to Boost ESCC Development by Regulating STAT1 - Shaofeng Zhang; Danqing Li; Haijun Wang; Bo Liu; Fan Du; Qing Wang (Cell Biochemistry and Biophysics, 2024)

Global response of soil biodiversity to climate and land use changes - Xiaoqian Shen; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; et al. (Journal of Cleaner Production, 2024)

Food-grade emulsion gels and oleogels prepared by all-natural dual nanofibril system from citrus fiber and glycyrrhizic acid - Shiqi Zhang; Ruijie Du; Qing Li; Mengyue Xu; Yunyi Yang; Suqiong Fang; Zhili Wan; Xiaoquan Yang (Food Research International, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

Resolving controversies surrounding carbon sinks from carbonate weathering - Xiaoyong Bai; Sirui Zhang; Pete Smith; Chaojun Li; Lian Xiong; Chaochao Du; Yingying Xue; Zilin Li; Mingkang Long; Minghui Li; Xiaoyun Zhang; Shu Yang; et al. (Science China Earth Sciences, 2024)

Effects of different curing concentrations and drying times on the microbial community structure and metabolites of dried Spanish mackerel - Jing Li; Yang Liu; Cai-yan Jiang; Xiao-qing Miao; Xiu-ping Dong; Ming Du; Peng-fei Jiang (Food Chemistry, 2024)

Stability of tryptophan-containing LOs in flaxseed oil and their response towards γ-tocopherol - Wan-zhen Li; Zi-liang Song; Jun-le Li; Jia-hui Yu; Du-jian Deng; Xiao-qing Cai; Martin J.T. Reaney; Zi-zhe Cai; Yong Wang (Food Chemistry, 2024)

Type 2 herpes simplex virus-induced anti-N-methyl-d-aspartate receptor encephalitis responsive to immunoglobulin monotherapy - Er-Chuang Li; Qi-Lun Lai; Tian-Yi Zhang; Bing-Qing Du; Jing Zhao; Meng-Ting Cai; Yin-Xi Zhang; Gao-Li Fang (Journal of NeuroVirology, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

Comparative study of decoupled- and coupled-based predictive models for seismically-induced slope displacements during shallow crustal earthquakes - Mao-Xin Wang; Chen-Yang Zhang; Dian-Qing Li; Wenqi Du (Engineering Geology, 2024)

An improved method for LEO orbit prediction using predicted accelerometer data - Junfeng Du; Xiaolei Dai; Yidong Lou; Yun Qing; Yaquan Peng; Xingang Li (GPS Solutions, 2024)

Effects of exogenous application of the strigolactone GR24 on quality and flavor components during postharvest storage of celery - Mengyao Li; Xiaoyan Li; Jiageng Du; Weilong Li; Ruiyuan He; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Qing Chen; Yong Zhang; Xiaorong Wang; et al. (Postharvest Biology and Technology, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

FSN-YOLO: Nearshore Vessel Detection via Fusing Receptive-Field Attention and Lightweight Network - Na Du; Qing Feng; Qichuang Liu; Hui Li; Shikai Guo (Journal of Marine Science and Engineering, 2024)
Vessel detection is critical for ensuring maritime transportation and navigational safety, creating a pressing need for detection methodologies that are more efficient, precise, and intelligent in the maritime domain. Nonetheless, accurately detecting vessels across multiple scales remains challenging due to the diversity in vessel types and locations, similarities in ship hull shapes, and disturbances from complex environmental conditions. To address these issues, we introduce an innovative FSN-YOLO framework that utilizes enhanced YOLOv8 with multi-layer attention feature fusion. Specifically, FSN-YOLO employs the backbone structure of FasterNet, enriching feature representations through super-resolution processing with a lightweight Convolutional Neural Network (CNN), thereby achieving a balance between processing speed and model size without compromising accuracy. Furthermore, FSN-YOLO uses the Receptive-Field Attention (RFA) mechanism to adaptively fine-tune the feature responses between channels, significantly boosting the network’s capacity to capture critical information and, in turn, improve the model’s overall performance and enrich the discriminative feature representation of ships. Experimental validation on the Seaship7000 dataset showed that, compared to the baseline YOLOv8l approach, FSN-YOLO considerably increased accuracy, recall rates, and mAP@0.5:0.95 by absolute margins of 0.82%, 1.54%, and 1.56%, respectively, positioning it at the forefront of current state-of-the-art models.

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Exposure estimation and neurotoxicity inhibition of dioxins in sensitive populations near domestic waste incineration plant through adverse outcome pathway - Qing Li; Yunxiang Li; Qikun Pu; Hao Yang; Meijin Du; Xinao Li; Yu Li; Xixi Li (Journal of Hazardous Materials, 2024)

Maternal prednisone exposure during pregnancy elevates susceptibility to osteoporosis in female offspring: The role of mitophagy/FNDC5 alteration in skeletal muscle - Zun-Yu Du; Hua-Long Zhu; Wei Chang; Yu-Feng Zhang; Qing Ling; Kai-Wen Wang; Jin Zhang; Quan-Bing Zhang; Xiu-Li Kan; Qu-Nan Wang; Hua Wang; Yun Zhou (Journal of Hazardous Materials, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Causes of episodic movement of the Baijiabao landslide based on multiple-time scale analysis - Zhiyong Fu; Dian-Qing Li; Shun Wang; Limin Zhang; Wenqi Du (Landslides, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Characterizing the dynamic resilient modulus of subgrade soil treated by BT-SAP subjected to freeze-thaw cycles - Xinzhuang Cui; Yefeng Du; Xiaoning Zhang; Jianwen Hao; Zhenhao Bao; Qing Jin; Xiangyang Li (Cold Regions Science and Technology, 2024)

Physiological and transcriptome analysis of acclimatory response to cold stress in marine red alga Pyropia yezoensis - Li-Hong Ma; Lin Tian; Yu-Qing Wang; Cong-Ying Xie; Guo-Ying Du (Algae, 2024)
Red macroalga Pyropia yezoensis is a high valuable cultivated marine crop. Its acclimation to cold stress is especially important for long cultivation period across winter in coasts of warm temperate zone in East Asia. In this study, the response of P. yezoensis thalli to low temperature was analyzed on physiology and transcriptome level, to explore its acclimation mechanism to cold stress. The results showed that the practical photosynthesis activity (indicated by ΦPSII and qP) was depressed and pigment allophycocyanin content was decreased during the cold stress of 48 h. However, the Fv/Fm and non-photochemical quenching increased significantly after 24 h, and the average growth rate of thalli also rebounded from 24 to 48 h, indicating a certain extent of acclimation to cold stress. On transcriptionally, the low temperature promoted the expression of differentially expressed genes (DEGs) related to carbohydrate metabolism and energy metabolism, while genes related to photosynthetic system were depressed. The increased expression of DEGs involved in ribosomal biogenesis and lipid metabolism which could accelerate protein synthesis and enhance the degree of fatty acid unsaturation, might help P. yezoensis thallus cells to cope with cold stress. Further co-expression network analysis revealed differential expression trends along with stress time, and corresponding hub genes play important roles in the systemic acquired acclimation to cold stress. This study provides basic mechanisms of P. yezoensis acclimation to cold temperature and may aid in exploration of functional genes for genetic breeding of economic macroalgae.

Silica nanoparticles conferring resistance to bacterial wilt in peanut (Arachis hypogaea L.) - Quanqing Deng; Suihua Huang; Hao Liu; Qing Lu; Puxuan Du; Haifen Li; Shaoxiong Li; Haiyan Liu; Runfeng Wang; Lu Huang; Dayuan Sun; Yahui Wu; et al. (Science of The Total Environment, 2024)

The priority leaching of lithium from spent LiFePO4 cathode without the oxidization - Jiawei Du; Jialin Qing; Kaiyuan Fang; Guiqing Zhang; Zuoying Cao; Qinggang Li; Mingyu Wang; Wenjuan Guan; Shengxi Wu (Resources, Conservation and Recycling, 2024)

Eighteen iridoids from the roots and rhizomes of Valeriana jatamansi and their protective effects against α-hemolysin - Yao Zhu; Peng-Ju Guo; Ao-Xue Ding; Liu Zheng; Gao-Xiang Du; Tong Chen; Guo-Qing Qin; Xiang-Gang Hu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Sinoflavonoids NJ and NK, anti-inflammatory prenylated flavonoids from the fruits of Podophyllum hexandrum Royle - Junyang Wang; Han Li; Yanhui Li; Aiping Yang; Sheng Bao; Yuntian Zhang; Qing Du; Zongping Zheng; Xiachang Wang (Natural Product Research, 2024)

Influences of regional site condition and grid size on seismic damage assessment of water distribution systems - Rongheng Zhao; Dian-Qing Li; Shi-Xiang Gu; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2024)

Long-term tralopyril exposure results in endocrinological and transgenerational toxicity: A two-generation study of marine medaka (Oryzias melastigma) - Bin Liu; Ping Li; Ren-Yan Du; Cun-Long Wang; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2024)

An analytical urban temperature model with building heterogeneity using geometric optical theory - Zunjian Bian; Tengyuan Fan; J.-L. Roujean; Dandan Wang; Mark Irvine; Shengbiao Wu; Biao Cao; Hua Li; Yongming Du; Qing Xiao; Qinhuo Liu (Remote Sensing of Environment, 2024)

Study of microscopic imbibition and formation plugging mechanism of the compact oil reservoir based on SEM and NMR analysis - Cheng Liu; Qing You; Tianru Wang; Bojie Zhou; Wei Peng; Yuechun Du; Yifei Liu; Yuyang Li; Caili Dai (Fuel, 2024)

Effect of ambient high-temperature on real driving emission tests of a light-duty gasoline vehicle - Rui Wang; Li Zhang; Jingde Peng; Jinlin Han; Baocheng Du; Baoli Gong; Haoyang Xue; Dajiang Tuo; Qing Zhang (Atmospheric Pollution Research, 2024)

A nanocarrier immersion vaccine encoding surface immunogenic protein confers cross-immunoprotection against Streptococcus agalactiae and Streptococcus iniae infection in tilapia - Ye Cao; Jia Liu; Gaoyang Liu; Hui Du; Tianqiang Liu; Tao Liu; Pengfei Li; Qing Yu; Gaoxue Wang; Erlong Wang (Fish & Shellfish Immunology, 2024)

Digital mapping of cultivated land soil organic matter in hill-mountain and plain regions - Hongxia Xie; Weiyou Li; Liangxia Duan; Hong Yuan; Qing Zhou; Zhe Luo; Huihui Du (Journal of Soils and Sediments, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

Effects of chalcogenophene π-bridges on benzodifuran-based polymers for high-performance organic solar cells - Xiaoru Xu; Xianda Li; Zongtao Wang; Jiagui Yu; Chao Li; Mengzhen Du; Qiang Guo; Qing Guo; Erjun Zhou (Chemical Engineering Journal, 2023)

Non-destructive fruit firmness evaluation using a soft gripper and vision-based tactile sensing - Jiahao Lin; Qing Hu; Jinming Xia; Liang Zhao; Xuan Du; Shanjun Li; Yaohui Chen; Xing Wang (Computers and Electronics in Agriculture, 2023)

Enolase-based nanovaccine immersion immunization induces robust immunity and protection against Streptococcus infection in tilapia - Jia Liu; Ye Cao; Haixiang Ma; Hui Du; Tianqiang Liu; Gaoxue Wang; Mingzhu Liu; Qing Wang; Pengfei Li; Erlong Wang (Aquaculture, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Biodegradability analysis of Dioxins through in silico methods: Model construction and mechanism analysis - Qing Li; Hao Yang; Ning Hao; Meijn Du; Yuanyuan Zhao; Yu Li; Xixi Li (Journal of Environmental Management, 2023)

BayLUP: A Bayesian framework for conditional random field simulation of the liquefaction-induced settlement considering statistical uncertainty and model error - Cong Miao; Zi-Jun Cao; Te Xiao; Dian-Qing Li; Wenqi Du (Gondwana Research, 2023)

Corrigendum to “Ginsenoside Rg1 alleviates ANIT-induced intrahepatic cholestasis in rats via activating farnesoid X receptor and regulating transporters and metabolic enzymes” [Chem Biol Interact. 324 (2020 Jun 1) 109062] - Qing Xiao; Shujun Zhang; Huina Ren; Ruoyang Du; Jiajun Li; Jinqiu Zhao; Yue Gao; Yali Zhu; Wenxiang Huang (Chemico-Biological Interactions, 2023)

Association between meteorological factors and varicella incidence: a multicity study in Yunnan Province, China - Hao Wang; Shanjun Huang; Zhaohan Wang; Hua Zhen; Zhuo Li; Wenqi Fan; Menghan Lu; Xin Han; Lanping Du; Meifang Zhao; Yuke Yan; Xinyao Zhang; et al. (Environmental Science and Pollution Research, 2023)

Two new constituents from the aerial parts of Salvia miltiorrhiza Bge - Fan Yang; Jia Li; Xin-Lei Du; Shi-Jun Wang; Xiang-Hao Xu; Yong-Qing Zhang; Ran Yang (Natural Product Research, 2023)

Seismic fragility and demand hazard analyses for earth slopes incorporating soil property variability - Wei Wang; Dian-Qing Li; Xiao-Song Tang; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2023)

Dynamic resilient modulus of heavy-haul subgrade silt subjected to freeze-thaw cycles: Experimental investigation and evolution analysis - Jianwen Hao; Xinzhuang Cui; Zhenhao Bao; Qing Jin; Xiangyang Li; Yefeng Du; Jialin Zhou; Xiaoning Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

Reduced bacterial resistance antibiotics with improved microbiota tolerance in human intestinal: Molecular design and mechanism analysis - Meijin Du; Zhixing Ren; Qing Li; Qikun Pu; Xinao Li; Youli Qiu; Yu Li (Journal of Hazardous Materials, 2023)

Mechanism analysis of synthetic musks-induced miscarriage risk in pregnant women: Molecular and adverse outcome pathways perspectives - Xixi Li; Rui Li; Meijin Du; Qing Li; Di Liu (Science of The Total Environment, 2023)

Auxiliary Bayesian updating of embankment settlement based on finite element model and response surface method - Huaming Tian; Dian-Qing Li; Zi-Jun Cao; Wenqi Du (Engineering Geology, 2023)

Heterogeneous Fe-Co dual-atom catalyst outdistances the homogeneous counterpart for peroxymonosulfate-assisted water decontamination: New surface collision oxidation path and diatomic synergy - Changqing Zhu; Fenxian Cun; Zhongwei Fan; Yu Nie; Qing Du; Fuqiang Liu; Weiben Yang; Aimin Li (Water Research, 2023)

Numerical-based seismic displacement hazard analysis for earth slopes considering spatially variable soils - Mao-Xin Wang; Qiang Wu; Dian-Qing Li; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

A thermal radiation directionality correction method for the surface upward longwave radiation of geostationary satellite based on a time-evolving kernel-driven model - Boxiong Qin; Biao Cao; Jean-Louis Roujean; Jean-Philippe Gastellu-Etchegorry; Sofia L. Ermida; Zunjian Bian; Yongming Du; Tian Hu; Hua Li; Qing Xiao; Shuisen Chen; Qinhuo Liu (Remote Sensing of Environment, 2023)

Responses of biofilm communities in a hybrid moving bed biofilm reactor-membrane bioreactor system to sulfadiazine antibiotic exposure - Xinbo Zhang; Sicong Zuo; Songya Li; Yutong Shang; Qing Du; Huizhong Wang; Wenshan Guo; Huu Hao Ngo (Bioresource Technology, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Molecularly imprinted polymers embedded with double perovskite quantum dots: A ratiometric fluorescence sensor for visible and fluorescent determination of Rhein - Rongkun Zhu; Zengcheng Du; Mingfang Zhu; Huanru Liang; Shumei Wang; Qing Zhou; Rui Li; Yulan Li; Chaoying Zeng; Wenhao Liu; Qiqing Chen (Chemical Engineering Journal, 2023)

Extending the record of dolabellane-type diterpenoids from the soft coral Clavularia viridis: Structures and stereochemistry - Ye-Qing Du; Yuan Gao; Yi Zang; Jia Li; Xu-Wen Li; Yue-Wei Guo (Phytochemistry, 2023)

Methane emission reduction oriented extracellular electron transfer and bioremediation of sediment microbial fuel cell: A review - Chong Xu; Shiquan Sun; Yifu Li; Yang Gao; Wei Zhang; Liu Tian; Tian Li; Qing Du; Jingju Cai; Lean Zhou (Science of The Total Environment, 2023)

In-silico analysis of atmospheric diffusion, crop planting degrading scheme, and health risk of dioxins from a domestic waste incineration plant - Qing Li; Xixi Li; Zhixing Ren; Meijn Du; Jiawen Yang; Luze Yang; Wei He; Hao Yang; Yuanyuan Zhao; Wenwen Gu; Wei Liu; Wenjin Zhao; et al. (Waste Management, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Perfluoroalkyl and polyfluoroalkyl substances (PFAS) adsorbed on microplastics in drinking water: Implications for female exposure, reproductive health risk and its mitigation strategies through in silico methods - Meijin Du; Qikun Pu; Xixi Li; Hao Yang; Ning Hao; Qing Li; Yuanyuan Zhao; Yu Li (Journal of Cleaner Production, 2023)

Intrinsic facet-dependent electrochemical activities of BiOBr nanosheets for Br- exchange in electrochemically switched ion exchange process - Jie Wang; Liang Zhang; Yasi Hu; Xiao Du; Xiaogang Hao; Qing Cao; Guoqing Guan; Zhong Liu; Jun Li; Shanxia Luo; Xiaowei An (Chemical Engineering Journal, 2023)

Azido azole-1,3,4-triazine fused energetic materials: A bioinspired strategy for tuning thermal stability and sensitivity of metal-free primary explosives via hierarchical hydrogen-bond self-assembly - Lei Yang; Wei Du; Jing Feng; Jinshan Li; Qing Ma (Chemical Engineering Journal, 2023)

Fibroblast Growth Factor 2 Levels in Patients with Major Depressive Disorder: A Meta-analysis - Yan-Li Wang; Yang Du; Lei Chen; Qing-Shan Liu; Yong Cheng (Journal of Molecular Neuroscience, 2023)

Rapid dissimilatory nitrate reduction to ammonium conserves bioavailable nitrogen in organic deficient soils - Yuxuan Wan; Qing Du; Yue Wu; Ruixiang Li; Xuejun Yan; Nan Li; Xin Wang (Soil Biology and Biochemistry, 2023)

High-consistency proton exchange membrane fuel cells enabled by oxygen-electron mixed-pathway electrodes via digitalization design - Zhiming Bao; Biao Xie; Weizhuo Li; Shenghui Zhong; Linhao Fan; Chasen Tongsh; Fei Gao; Qing Du; Mohamed Benbouzid; Kui Jiao (Science Bulletin, 2023)

Simultaneous interfacial and bulk defect passivation and interface energy band alignment optimization via In(SCN2H4)3Cl3 diffusion doping for inverted perovskite solar cells - Dong Yang; Yujuan Weng; Zhitao Shen; Mengqi Jin; Hu Shen; Qing Du; Jihong Zheng; Fumin Li; Chong Chen (Chemical Engineering Journal, 2023)

Synergy of yolk-shelled structure and tunable oxygen defect over CdS/CdCO3-CoS2: Wide band-gap semiconductors assist in efficient visible-light-driven H2 production and CO2 reduction - Siyi Zhang; Shiwen Du; Yumin Wang; Ziwu Han; Xu Li; Guojun Li; Qing Hu; Hu Xu; Chunqing He; Pengfei Fang (Chemical Engineering Journal, 2023)

Characteristic analysis of s-Fe/Cu two-component micro-electrolysis materials and degradation of dye wastewater - Xiaosen Du; Jin Liu; Qing Liu; Guiju Li; Yongqing Jiang; Yaxin Zhang (Environmental Science and Pollution Research, 2023)

An angular normalization method for temperature vegetation dryness index (TVDI) in monitoring agricultural drought - Zunjian Bian; J.L. Roujean; Tengyuan Fan; Yadong Dong; Tian Hu; Biao Cao; Hua Li; Yongming Du; Qing Xiao; Qinhuo Liu (Remote Sensing of Environment, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

Mechanisms of chromatin-based epigenetic inheritance - Wenlong Du; Guojun Shi; Chun-Min Shan; Zhiming Li; Bing Zhu; Songtao Jia; Qing Li; Zhiguo Zhang (Science China Life Sciences, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Complete chloroplast genomes of two medicinal Swertia species: the comparative evolutionary analysis of Swertia genus in the Gentianaceae family - Qing Du; Jing Li; Liqiang Wang; Haimei Chen; Mei Jiang; Zhuoer Chen; Chuanbei Jiang; Haidong Gao; Bin Wang; Chang Liu (Planta, 2022)

A new perspective to improve the treatment of Lianhuaqingwen on COVID-19 and prevent the environmental health risk of medication - Wenwen Gu; Yuanyuan Zhao; Luze Yang; Meijin Du; Qing Li; Zhixing Ren; Xixi Li (Environmental Science and Pollution Research, 2022)

Assessment of microbial α-diversity in one meter squared topsoil - Shuzhen Li; Xiongfeng Du; Kai Feng; Yueni Wu; Qing He; Zhujun Wang; Yangying Liu; Danrui Wang; Xi Peng; Zhaojing Zhang; Arthur Escalas; Yuanyuan Qu; et al. (Soil Ecology Letters, 2022)

VGLUT3 neurons in median raphe control the efficacy of spatial memory retrieval via ETV4 regulation of VGLUT3 transcription - Aodi He; Chen Zhang; Xiao Ke; Yao Yi; Quntao Yu; Tongmei Zhang; Hongyan Yu; Huiyun Du; Hao Li; Qing Tian; Ling-Qiang Zhu; Youming Lu (Science China Life Sciences, 2022)

A Dual-Layer Equivalent-Source Method for Deriving Gravity Field Vector and Gravity Tensor Components from Observed Gravity Data - Duan Li; Qing Liang; Jinsong Du; Chao Chen (Pure and Applied Geophysics, 2022)

D-aspartic acid protects against gingival fibroblasts inflammation by suppressing pyroptosis - Xuechun Du; Baosheng Li; Qing Cai; Shuwei Qiao; Zixuan Wang; Zhen Li; Yuyang Li; Weiyan Meng (Molecular Biology Reports, 2022)

Hyperlipidemia patients carrying LDLR splicing mutation c.1187-2A>G respond favorably to rosuvastatin and PCSK9 inhibitor evolocumab - Xiaoyu Zhang; Qianqian Liu; Hongfu Zhang; Chengcheng Tan; Qiangfeng Zhu; Saiyong Chen; Yinglong Du; Haitao Yang; Qingli Li; Chengqi Xu; Chun Wu; Qing K. Wang (Molecular Genetics and Genomics, 2022)

The complete chloroplast genome sequence of Clerodendranthus spicatus, a medicinal plant for preventing and treating kidney diseases from Lamiaceae family - Qing Du; Mei Jiang; Sihui Sun; Liqiang Wang; Shengyu Liu; Chuanbei Jiang; Haidong Gao; Haimei Chen; Yong Li; Bin Wang; Chang Liu (Molecular Biology Reports, 2022)

Two-stage Bayesian experimental design optimization for measuring soil–water characteristic curve - Shao-Lin Ding; Dian-Qing Li; Zi-Jun Cao; Wenqi Du (Bulletin of Engineering Geology and the Environment, 2022)

Zinc finger and BTB domain-containing protein 20 aggravates angiotensin II-induced cardiac remodeling via the EGFR-AKT pathway - Fangfang Li; Miaomiao Du; Yiming Yang; Zhu Wang; Hu Zhang; Xiaoyu Wang; Qing Li (Journal of Molecular Medicine, 2022)

Cellular metabolic basis of altered immunity in the lungs of patients with COVID-19 - Shuangyan Li; Fuxiaonan Zhao; Jing Ye; Kuan Li; Qi Wang; Zhongchao Du; Qing Yue; Sisi Wang; Qi Wu; Huaiyong Chen (Medical Microbiology and Immunology, 2022)

Azospirillum tabaci sp. nov., a bacterium isolated from rhizosphere soil of Nicotiana tabacum L - Yan-Qing Duan; Xing-Kui Zhou; Neeli Habib; Shi-Qiang Gao; Li-Min Dong; Xiao-Fei Liu; Yang-Mei Shi; Wen-Jun Li; Gang Du (Archives of Microbiology, 2022)

MiR-146a Negatively Regulates Aspergillus fumigatus-Induced TNF-α and IL-6 Secretion in THP-1 Macrophages - Jianbo Tong; Zhimin Duan; Rong Zeng; Leilei Du; Song Xu; Liwei Wang; Yuzhen Liu; Qing Chen; Xu Chen; Min Li (Mycopathologia, 2021)

The optimal number of embryo cells for effective pregnancy and decrease of multiple pregnancy rate in frozen-thawed embryo transfer - Xu-Li Zhu; Zhi-Ming Zhao; Yuan-Jie Du; Liang Zhou; Yue Wang; Qing-Yun Sun; Gui-Min Hao; Bu-Lang Gao (Human Cell, 2021)

LncRNA XIST Promotes Migration and Invasion of Papillary Thyroid Cancer Cell by Modulating MiR-101-3p/CLDN1 Axis - Yong-Liang Du; Yan Liang; Yan Cao; Le Liu; Jian Li; Guang-Qing Shi (Biochemical Genetics, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Steeper spatial scaling patterns of subsoil microbiota are shaped by deterministic assembly process - Xiongfeng Du; Ye Deng; Shuzhen Li; Arthur Escalas; Kai Feng; Qing He; Zhujun Wang; Yueni Wu; Danrui Wang; Xi Peng; Shang Wang (Molecular Ecology, 2021)
Although many studies have investigated the spatial scaling of microbial communities living in surface soils, very little is known about the patterns within deeper strata, nor is the mechanism behind them. Here, we systematically assessed spatial scaling of prokaryotic biodiversity within three different strata (Upper: 0–20 cm, Middle: 20–40 cm, and Substratum: 40–100 cm) in a typical grassland by examining both distance–decay (DDRs) and species–area relationships (SARs), taxonomically and phylogenetically, as well as community assembly processes. Each layer exhibited significant biogeographic patterns in both DDR and SAR ( p β and z values, respectively, ranged from 0.016 ± 0.005 to 0.023 ± 0.005 and 0.065 ± 0.002 to 0.077 ± 0.004 across soil strata, and both increased with depth. Moreover, the prokaryotic community in grassland soils assembled mainly according to deterministic rather than stochastic mechanisms. By using normalized stochasticity ratio (NST) based on null model, the relative importance of deterministic ratios increased from 48.0 to 63.3% from Upper to Substratum, meanwhile a phylogenetic based method revealed average βNTI also increased with depth, from −5.29 to 19.5. Using variation partitioning and distance approaches, both geographic distance and soil properties were found to strongly affect biodiversity structure, the proportions increasing with depth, but spatial distance was always the main underlying factor. These indicated increasingly deterministic proportions in accelerating turnover rates for spatial assembly of prokaryotic biodiversity. Our study provided new insights on biogeography in different strata, revealing importance of assembly patterns and mechanisms of prokaryote communities in below‐surface soils.

Nitrogen and litter addition decreased sexual reproduction and increased clonal propagation in grasslands - Zimeng Li; Jinfeng Wu; Qing Han; Kunyan Nie; Jiani Xie; Yufei Li; Xinyu Wang; Haibo Du; Deli Wang; Jushan Liu (Oecologia, 2021)

Holocene aeolian activities linked to Indian summer monsoon in the middle reaches of the Yarlung Zangbo River - Tuoyu Li; Jifeng Zhang; Yongqiu Wu; Shisong Du; Duowen Mo; Yinan Liao; Zhitong Chen; Jianbao Liu; Qing Li (Journal of Geographical Sciences, 2020)

Solanrubiellin A, a hydroanthraquinone dimer with antibacterial and cytotoxic activity from Solanum lyratum - Hui Chen; Kun Du; Yan-Jun Sun; Zhi-You Hao; Yan-Li Zhang; Jiang Bai; Qing-Hua Wang; Hai-Yu Hu; Wei-Sheng Feng (Natural Product Research, 2020)

Zircon U-Pb-Hf isotopes and geochemistry of Jurassic igneous rocks from the southern Zhangguangcai Range, NE China: constraints on magmatism, petrogenesis and tectonic implications - Zuo-Zhen Han; Xiang Ren; Hans-Peter Schertl; Xu-Ping Li; Zhi-Gang Song; Qing-Xiang Du; Chao Han; Wen-Jian Zhong; Li-Hua Gao (International Geology Review, 2020)

The ultraviolet–visible absorbance and fluorescence characterization of dissolved organic matter derived from the leaf litter of Populus simonii, Artemisia desertorum, Salix cheilophila, and Populus tomentosa - Li Zhao; Congcong Du; Qing Zhang; Chao Sun; Shidong Wang; Shaohe Luo (Environmental Science and Pollution Research, 2020)

Assessing major factors impacts on the hydrogeochemistry in a riverside alluvial aquifer, northeast China - Li Wang; Tao Du; Qing Hu; Sijie Lin; Mingzhu Liu; Honghan Chen (Arabian Journal of Geosciences, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Drug Elimination Alteration in Acute Lymphoblastic Leukemia Mediated by Renal Transporters and Glomerular Filtration - Yue Zhou; Bin Du; Min Kan; Shang Chen; Bo-Hao Tang; Ai-Qing Nie; Pan-Pan Ye; Hai-Yan Shi; Guo-Xiang Hao; Xiu-Li Guo; Qiu-Ju Han; Yi Zheng; et al. (Pharmaceutical Research, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Efficacy coefficient method assisted quadruple-activities 3D-QSAR pharmacophore model for application in environmentally friendly PAE molecular modification - Meijin Du; Youli Qiu; Qing Li; Yu Li (Environmental Science and Pollution Research, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

Genetic dissection of yield-related traits via genome-wide association analysis across multiple environments in wild soybean (Glycine soja Sieb. and Zucc.) - Dezhou Hu; Huairen Zhang; Qing Du; Zhenbin Hu; Zhongyi Yang; Xiao Li; Jiao Wang; Fang Huang; Deyue Yu; Hui Wang; Guizhen Kan (Planta, 2020)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

First report of tobacco curly shoot virus infecting Malvastrum coromandelianum in China - Pengbai Li; Chenchen Jing; Ke Li; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Journal of Plant Pathology, 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Higher phenotypic plasticity does not confer higher salt resistance to Robinia pseudoacacia than Amorpha fruticosa - Xiao Guo; Xiao-Huang Ren; Franziska Eller; Ming-Yan Li; Ren-Qing Wang; Ning Du; Wei-Hua Guo (Acta Physiologiae Plantarum, 2018)

Soil physical properties response to tillage practices during summer fallow of dryland winter wheat field on the Loess Plateau - Jian-Fu Xue; Ai-Xia Ren; Hui Li; Zhi-Qiang Gao; Tian-Qing Du (Environmental Science and Pollution Research, 2018)

Helpers of the Giant Babax cheat for an immediate reward when they provision the brood - Li-Qing Fan; Xin-Wei Da; Juan-Juan Luo; Li-Li Xian; Guo-Liang Chen; Bo Du (Journal of Ornithology, 2018)

Inflammation Induced by Candida parapsilosis in THP-1 Cells and Human Peripheral Blood Mononuclear Cells (PBMCs) - Zhimin Duan; Xu Chen; Leilei Du; Caixia Liu; Rong Zeng; Qing Chen; Min Li (Mycopathologia, 2017)

Application of DNA barcodes for testing hypotheses on the role of trait conservatism and adaptive plasticity in Acer L. section Palmata Pax (Sapindaceae) - Jian Gao; Pei-Chun Liao; Wan-Heng Meng; Fang K. Du; Jun-Qing Li (Brazilian Journal of Botany, 2017)

Effects of the nitrification inhibitor dicyandiamide (DCD) on N2Oemissions and the abundance of nitrifiers and denitrifiers in two contrasting agricultural soils - Qing Wang; Hang-Wei Hu; Ju-Pei Shen; Shuai Du; Li-Mei Zhang; Ji-Zheng He; Li-Li Han (Journal of Soils and Sediments, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The septin protein S ep4 facilitates host infection by plant fungal pathogens via mediating initiation of infection structure formation - Hui‐Qiang Feng; Gui‐Hua Li; Shun‐Wen Du; Song Yang; Xue‐Qian Li; Paul de Figueiredo; Qing‐Ming Qin (Environmental Microbiology, 2017)
Summary Many phytopathogenic fungi use infection structures (IFSs, i.e., appressoria and infection cushions) to penetrate host cuticles. However, the conserved mechanisms that mediate initiation of IFS formation in divergent pathogens upon sensing the presence of host plants remain obscure. Here, we demonstrate that a conserved septin gene SEP4 plays crucial roles in this process. Disruption of SEP4 in the plant grey mould fungus Botrytis cinerea completely blocked IFS formation and abolished the virulence of Δ Bcsep4 mutants on unwounded hosts. During IFS formation, mutants lacking SEP4 could produce reactive oxygen species (ROS) normally. Inhibition of ROS production in strains harbouring the SEP4 gene resulted in disordered assembly of Sep4 and the subsequent failure to form infection cushions, suggesting that proper Sep4 assembly regulated by ROS is required for initiation of IFS formation and infection. Moreover, loss of SEP4 severely impaired mutant conidiation, melanin and chitin accumulation in hyphal tips and lesion expansion on wounded hosts, but significantly promoted germ tube elongation and sclerotium production. SEP4 ‐mediated fungal pathogenic development, including IFS formation, was validated in the hemibiotroph Magnaporthe oryzae . Our findings indicate that Sep4 plays pleiotropic roles in B. cinerea development and specifically facilities host infection by mediating initiation of IFS formation in divergent plant fungal pathogens in response to ROS signaling.

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

Free multi-floor indoor space extraction from complex 3D building models - Qing Xiong; Qing Zhu; Zhiqiang Du; Sisi Zlatanova; Yeting Zhang; Yan Zhou; Yun Li (Earth Science Informatics, 2017)

Three-Dimensional Reconstruction and Visualization of Human Enamel Ex Vivo Using High-Frequency Ultrasound - Juan Du; Xue-Li Mao; Peng-Fei Ye; Qing-Hua Huang (Journal of Medical and Biological Engineering, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Effects of dicyandiamide and acetylene on N2O emissions and ammonia oxidizers in a fluvo-aquic soil applied with urea - Qing Wang; Li-Mei Zhang; Ju-Pei Shen; Shuai Du; Li-Li Han; Ji-Zheng He (Environmental Science and Pollution Research, 2016)

Nitrogen fertiliser-induced changes in N2O emissions are attributed more to ammonia-oxidising bacteria rather than archaea as revealed using 1-octyne and acetylene inhibitors in two arable soils - Qing Wang; Li-Mei Zhang; Ju-Pei Shen; Shuai Du; Li-Li Han; Ji-Zheng He (Biology and Fertility of Soils, 2016)

Sedimentary characterization of the Upper Paleozoic coal-bearing tight sand strata, Daniudi Gas Field, Ordos Basin, China - Wei Du; Zaixing Jiang; Qing Li; Ying Zhang (Journal of Earth Science, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

Heat-induced unfolding of apo-CP43 studied by fluorescence spectroscopy and CD spectroscopy - Qing-Jie Xiao; Zai-Geng Li; Jiao Yang; Qing He; Lei Xi; Lin-Fang Du (Photosynthesis Research, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Isoflurane Protects Against Injury Caused by Deprivation of Oxygen and Glucose in Microglia Through Regulation of the Toll-Like Receptor 4 Pathway - Hai-Fei Xiang; Dong-Hang Cao; Yan-Qing Yang; Hui-Qin Wang; Li-Jun Zhu; Bin-Hao Ruan; Jing Du; Ming-Cang Wang (Journal of Molecular Neuroscience, 2014)

Simultaneous determination by UPLC-MS/MS of seven bioactive compounds in rat plasma after oral administration of Ginkgo biloba tablets: application to a pharmacokinetic study - Wen-ping Wang; Na Liu; Qian Kang; Pei-pei Du; Yi Lan; Bo-chen Zhao; Yan-yan Chen; Qing Zhang; Hui Li; Ye-wen Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Atorvastatin inhibits hyperglycemia-induced expression of osteopontin in the diabetic rat kidney via the p38 MAPK pathway - Li Zuo; Yong Du; Man Lu; Junling Gao; Ruolei Hu; Sumei Zhang; Yi Wang; Huaqing Zhu; Qing Zhou; Wei Wei; Yuan Wang (Molecular Biology Reports, 2014)

A theoretical study on the mechanism of a superficial mutation inhibiting the enzymatic activity of CYP1A2 - Li-Na Ma; Zhen-Zhen Du; Peng Lian; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Comparative pharmacokinetics of borneol in cerebral ischemia-reperfusion and sham-operated rats - Pan Xu; Ying Li; Shou-Ying Du; Yang Lu; Jie Bai; Qing-li Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Reduction of methylviologen-mediated oxidative stress tolerance in antisense transgenic tobacco seedlings through restricted expression of StAPX - Wei-hong Sun; Yong Wang; Hua-gang He; Xue Li; Wan Song; Bin Du; Qing-wei Meng (Journal of Zhejiang University-SCIENCE B, 2013)

TNFAIP3 gene polymorphisms confer risk for Behcet’s disease in a Chinese Han population - Hong Li; Qing Liu; Shengping Hou; Liping Du; Qingyun Zhou; Yan Zhou; Aize Kijlstra; Zheng Li; Peizeng Yang (Human Genetics, 2013)

The TRIMCyp genotype in four species of macaques in China - Chang-Qing Yu; Lei Na; Xiao-Ling Lv; Jian-Dong Liu; Xiao-Ming Liu; Fang Ji; Yong-Hui Zheng; Hong-Li Du; Xian-Gang Kong; Jian-Hua Zhou (Immunogenetics, 2013)

Interpretation of magnetic anomalies by horizontal and vertical derivatives of the analytic signal - Guo-Qing Ma; Xiao-Juan Du; Li-Li Li; Ling-Shun Meng (Applied Geophysics, 2012)

Effects of total dissolved gas supersaturated water on lethality and catalase activity of Chinese sucker (Myxocyprinus asiaticus Bleeker) - Shi-chao Chen; Xiao-qing Liu; Wen Jiang; Ke-feng Li; Jun Du; Dan-zhou Shen; Quan Gong (Journal of Zhejiang University-SCIENCE B, 2012)

An integrated approach to demonstrating the ANR pathway of proanthocyanidin biosynthesis in plants - Qing-Zhong Peng; Yue Zhu; Zhong Liu; Ci Du; Ke-Gang Li; De-Yu Xie (Planta, 2012)

Morphological and molecular evidence for natural hybridization in sympatric population of Roscoea humeana and R. cautleoides (Zingiberaceae) - Guang-Hui Du; Zhi-Qiang Zhang; Qing-Jun Li (Journal of Plant Research, 2012)

Environmental and health challenges of the global growth of electronic waste - Qiang Liu; Shu Juan Shi; Li Qing Du; Yan Wang; Jia Cao; Chang Xu; Fei Yue Fan; John P. Giesy; Markus Hecker (Environmental Science and Pollution Research, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Growth rate, catalase and superoxide dismutase activities in rock carp (Procypris rabaudi Tchang) exposed to supersaturated total dissolved gas - Xiao-qing Liu; Ke-feng Li; Jun Du; Jia Li; Ran Li (Journal of Zhejiang University-SCIENCE B, 2011)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

Neurochip based on light-addressable potentiometric sensor with wavelet transform de-noising - Qing-jun Liu; Wei-wei Ye; Hui Yu; Ning Hu; Li-ping Du; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Polymorphism of chicken myocyte-specific enhancer-binding factor 2A gene and its association with chicken carcass traits - Yan Zhou; Yiping Liu; Xiaosong Jiang; Huarui Du; Xiaocheng Li; Qing Zhu (Molecular Biology Reports, 2010)

Reversal of coenzyme specificity and improvement of catalytic efficiency of Pichia stipitis xylose reductase by rational site-directed mutagenesis - Qi-Kai Zeng; Hong-Li Du; Jing-Fang Wang; Dong-Qing Wei; Xiao-Ning Wang; Yi-Xue Li; Ying Lin (Biotechnology Letters, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

A study on cellular automata based on relational databases and spatio-temporal simulations of culture diffusion - Ping Luo; Qing-yun Du; Su-fang He; Sen Li; Gallagher Michael; Hui-en Niu (Chinese Geographical Science, 2002)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)